PENGARUH KINERJA PETUGAS DALAM PENGAMBILAN (RETRIVAL) REKAM MEDIS RAWAT JALAN TERHADAP PENGGUNAAN TRACER DI RUMAH SAKIT UNIVERSITAS SUMATERA UTARA BULAN JULI SAMPAI AGUSTUS TAHUN 2019 - NAINGGOLAN, YUDICA ROSALINA (JURNAL ILMIAH SIMANTEK, 2021)
Officer performance is a statement of an activity or pattern of behavior or application of learning abilities to complete a process related to predetermined specifications or standards. Use of tracer or outguide and guidance cards used to replace medical record files taken for various staff needs in the storage of North Sumatra University Hospital. The population was 4 people and the sample was 4 people as the total sampling. The instrument in this study used a questionnaire, the respondents were storage officers and unit heads at the North Sumatra University Hospital. From the research results it was found that the influence of officer performance according to the majority of respondents in the category of strongly agree was 2 people (50.0), and 2 people agreed (SO.O) with manual calculations. Based on the results of the research conducted, it can be concluded that the influence of officer performance in taking outpatient medical records on the use of tracers at North Sumatra University Hospital.